Australian singer, American features: Performing authenticity in country music. (January 2017) - Duncan, Daniel
Abstract: Country music, while performed globally, is strongly associated with the Southern United States. Non-American Anglophone country artists like Keith Urban, an Australian country singer, thus represent transnational dialect contact. I examine Urban's use of three variables: price monophthongization, (ING), and coda /r /. When compared to American artists, Urban heavily style shifts between speech and song; however, the artists perform similarly in song. I argue that authenticity is commodified, pushing artists to perform authenticity by indexing values enregistered as authentic. Urban strongly style shifts because as an outsider, language use is the only strategy available for such a performance. Highlights: Anglophone country singers style shift toward Southern American English features. Non-American artists style shift most dramatically. Artists' sung features are strikingly similar regardless of background. Artists perform authenticity by indexing values enregistered as authentic. Non-American country singers may only style shift to perform authenticity.